Evaluation of Rosuvastatin Therapy on SIRT1 Gene Expression in Patients with Multiple Sclerosis: An Uncontrolled Clinical Trial - Shakiba Batoee, Pharm.D; Maryam Etminaniesfahani, Pham.D, Ph.D; Mehrdokht Mazdeh, MD, Specialist in neurological diseases; Alireza Soltanian, Ph.D; Fatemeh Nouri, PharmD, PhD (Elsevier, 2023)
ABSTRACT: Background: Multiple sclerosis (MS) is a chronic autoimmune disease. Current medications have some limitations such as low efficacy and high side effects. In recent years, statins have been raised as potential therapeutics for MS treatment with minimal complications. In addition, patient monitoring using suitable molecular markers is necessary for treatment response evaluation. Objective: The aim of the present study was the evaluation of SIRT1 gene expression changes following rosuvastatin therapy in patients with MS. Methods: This before-after uncontrolled clinical trial study was performed on 25 patients with MS. Patients were treated with 20 mg rosuvastatin daily for 3 months. The Expanded Disability Status Scale (EDSS) was measured before and after statin therapy. Blood samples were taken from patients 2 times, before and after statin therapy, and centrifuged for white blood cell isolation. Total RNA was extracted using RNX-plus reagent, and complementary DNA was synthesized using Pars Tous cDNA Synthesis Kit. Real-time polymerase chain reaction was done using SYBR blue master mix and gene-specific primers in Roche light cycler. Patients' information was recorded using a checklist. Data analysis was performed using SPSS version 23 and Graph Pad version 9 software and P < 0.05 was considered a significant level. Results: SIRT1 was significantly upregulated in MS patients after statin therapy. Subsequently, EDSS of patients was decreased along with the increase in SIRT1 gene expression, although EDSS changes were not significant (P > 0.05). Pearson correlation test showed no significant relationship between EDSS and SIRT1 gene expression (P > 0.05). No significant relationship was observed between SIRT1 expression or EDSS levels with patients' age, sex, weight, height, and body mass index and administrated drugs (P > 0.05). Conclusions: SIRT1 potentially is a sensitive and reliable biomarker for patients with MS monitoring during statin therapy.